Swine applied ethology methods for a model of mild traumatic brain injury - Luo, Yunzhi (Kansas State University, 2017)
Stressors and stress responses are part of everyday life, for both humans and animals. Organisms evolved well-developed mechanisms to cope with most stressors, and to recover from stress responses. Nevertheless, severe acute stressors and chronic stressors lead to health problems. Traumatic brain injury (TBI) is defined as malfunctioning and pathology of the brain caused by external mechanical forces. This physical and psychological stressor may lead to long-term damage on both physiology and psychology mechanisms. Traumatic brain injury becomes a public health issue for millions of soldiers, veterans and general public, who suffer from its aftermath and reduced quality of life. To understand TBI, human patients and rodents models were extensively studied. In recent years, miniswine were utilized to research the histopathology of TBI. They serve as a better human brain model because their nervous system is more anatomically relevant than rodents, their brains have similar white:grey matter ratios as humans, and they have similar cognitive abilities as humans. Despite the progresses in pathology and histology work among miniswine models of TBI, there were not validated behavior tests for this new animal model. This thesis introduced two behavior-tests for Yucatan miniboar models. The first study was conducted to validate a modified human approach test (HAT) specifically designed for Yucatan miniboars for mild TBI experiments. This test was originally validated and widely used for commercial pigs. The current test was designed around the housing and animal care, with the experimental performing the test outside of pens where pigs were individually housed. Animals were treated with a single blast wave (BLAST) or anesthesia only (control, SHAM), and were tested 3 days before the treatment (baseline) and 3 consecutive days after the treatment. During the test, the spatial positions (Climb, Close, Mid and Far) and structural positions (Stand, Lie) were measured. Climb and Close were collectively named approach behaviors, and Mid and Far Move away behaviors. Results showed that this test had high reliability, and was sensitive to acute effects of TBI: BLAST-treated pigs showed decreased approach behaviors and increased move away behaviors following the treatment, compared to the baseline. The second experiment was conducted to develop automated data collection methods to monitor circadian active and inactive behaviors of miniboars. Using the same experimental design as described previously, Fitbit Zip, a commercially available accelerometer with an embedded algorithm (Fitbit, San Francisco, CA), was tested. When attached to ear tags, Fitbit Zip was validated to be recording head movements without locomotion, which were oral-nasal-facial (ONF) behaviors. Results showed that Fitbit Zips best-detected behavior changes following TBI at 2-hour observation intervals. BLAST animals showed decreased ONF behaviors during the day especially around the feeding time, which were also when the pigs were most active. Both behavior-tests were shown to be reliable and useful in measuring behavior changes following TBI in Yucatan miniboar models. Measures of behavior were shown to be a promising and valuable addition to the biomedical research utilizing large animal models. These advances in knowledge and technology could also benefit farm animal production.
Keywords: Swine; Human approach test; Automated loggers; Behavior; Locomotion